2009
DOI: 10.1080/10789669.2009.10390885
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Displacement and Mixing Ventilation Systems for a Patient Ward

Abstract: In hospital patient wards, exhalation flow from a patient with airborne infectious diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 19 publications
5
72
0
1
Order By: Relevance
“…They indicated that it should be possible to reduce the risk of aerosol transmission by altering the ventilation parameters in healthcare environments. This has been verified by our previous study [5] which showed that ventilation systems play a very important role in the contaminant distribution in an inpatient room. Qian et al [6] indicated that the downward laminar airflow pattern recommended by the CDC was impossible to achieve due to turbulent flow mixing and thermal buoyancy.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…They indicated that it should be possible to reduce the risk of aerosol transmission by altering the ventilation parameters in healthcare environments. This has been verified by our previous study [5] which showed that ventilation systems play a very important role in the contaminant distribution in an inpatient room. Qian et al [6] indicated that the downward laminar airflow pattern recommended by the CDC was impossible to achieve due to turbulent flow mixing and thermal buoyancy.…”
Section: Introductionsupporting
confidence: 79%
“…Our previous study [5] concluded that the tracer gas and 3-mm particles can be used to simulate contaminant release from a patient if the release is at a negligible velocity. This type of release includes breathing and talking.…”
Section: Simulation Of Contaminant By Tracer Gas and Particles Due Tomentioning
confidence: 99%
“…It should be highlighted that the influence of boundary conditions could be comparable to that of the air distribution methods. In addition, the relative importance of the 2 functions of DV, namely diluting pollutants vertically and increasing pollutants dispersion horizontally, may change with distance and vertical location of the exhaust opening . It is therefore important to clarify the exact boundary conditions when interpreting a specific finding.…”
Section: Current Understanding Of Airborne Transmission Indoorsmentioning
confidence: 99%
“…Well-mixed ventilation (WMV) is common for commercial buildings and residences where the air conditioning system operates. BDV and WMV are two widely utilized schemes and are also wellstudied in previous literature (Yin et al 2009;Lai and Wong 2010). Therefore, these two ventilation schemes were applied in the experimentation.…”
Section: Experimental Apparatus and Measurementsmentioning
confidence: 99%